2018
DOI: 10.2147/clep.s160018
|View full text |Cite
|
Sign up to set email alerts
|

Rising trends in pancreatic cancer incidence and mortality in 2000–2014

Abstract: BackgroundThe morbidity and mortality of pancreatic cancer vary considerably around the world. The aim of this study was to characterize and evaluate recent changes in incidence and incidence-based mortality in the USA.MethodsIncidence and incidence-based mortality data were based on the 18 Surveillance, Epidemiology, and End Results (SEER) registries through SEER*Stat software. We adopted joinpoint regression to analyze the temporal trends stratified by age, gender, ethnicity, stage, tumor site, and size.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 26 publications
(25 reference statements)
2
52
2
1
Order By: Relevance
“…Our results are consistent with other studies of Asian patients that reported an increase in incidence and mortality rates in the last 20 years. Wu et al concluded that age-adjusted incidence and incidence-based mortality for PAC increased during 2000-2014, whereas mortality rates increased during 2000-2005 but decreased during 2005-2014 [22]. According to their findings, based on 119,412 cases of PAC extracted from 18 SEER registries, both incidence and mortality trends increased during the study period, irrespective of ethnicity [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with other studies of Asian patients that reported an increase in incidence and mortality rates in the last 20 years. Wu et al concluded that age-adjusted incidence and incidence-based mortality for PAC increased during 2000-2014, whereas mortality rates increased during 2000-2005 but decreased during 2005-2014 [22]. According to their findings, based on 119,412 cases of PAC extracted from 18 SEER registries, both incidence and mortality trends increased during the study period, irrespective of ethnicity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al concluded that age-adjusted incidence and incidence-based mortality for PAC increased during 2000-2014, whereas mortality rates increased during 2000-2005 but decreased during 2005-2014 [22]. According to their findings, based on 119,412 cases of PAC extracted from 18 SEER registries, both incidence and mortality trends increased during the study period, irrespective of ethnicity [22]. In China, there was a significant increase in newly diagnosed pancreatic cancer cases and pancreatic cancer-attributed deaths from 2009 to 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the number of patients diagnosed with pancreatic cancer worldwide, according to GLOBOCAN 2012, was 337,872, which means that the incidence increased by 121,046 patients in 6 years [13]. Recent advances in imaging and other diagnostic tools may have contributed to the apparent increase in pancreatic cancer incidence because more patients are diagnosed in the early stages of the disease [14]. This may have also affected the 5-year survival estimates.…”
Section: Trendsmentioning
confidence: 99%
“…Pancreatic Ductal Adenocarcinoma (PDA) is the most common form of pancreatic malignancy but is typically diagnosed only in late-stage disease, hence both the incidence and deaths attributable to PDA continue to increase (7,8). At present, there is no clinical procedure that can accurately detect early asymptomatic PDA, largely due to the lack of specific biomarkers of disease (9,10), hence there is an urgent need for better predictors of tumour development and progression in this patient group with extremely poor prognosis.…”
Section: Introductionmentioning
confidence: 99%